THE CONCEPT OF VECTOR AND ITS PROPERTIES (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the concept of a vector and its basic properties. Vectors are mathematical objects that have direction and magnitude, and they are widely used in physics and engineering. The article discusses in detail the main types of vectors, their algebraic and geometric properties, and the operations performed on them, including addition, subtraction, scalar and vector multiplication. It also contains information about the real-world application of vectors and their important properties. The article will be useful to anyone interested in mathematics, students and teachers.